ANALYSIS OF ACADEMIC SUPERVISION AND INDEPENDENT TRAINING ON TEACHER PERFORMANCE WITH COMPENSATION AS AN INTERVENTING VARIABLEAT STATE MIDDLE SCHOOL 1 PINTU RIME GAYO, BENER MERIAH REGENCY - Aunan; Sri Rahayu; Mesra B (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Improving the quality of education at the junior high school level is highly dependent on teacher performance as the main actors in the learning process. This study aims to analyze the effect of academic supervision and independent training on teacher performance, with compensation as an intervening variable at SMP Negeri 1 Pintu Rime Gayo, Bener Meriah Regency. This study uses a quantitative approach with Partial Least Squares (PLS) analysis. The population in this study were all 64 teachers, with a saturated sampling technique. The results show that academic supervision and independent training have a positive and significant effect on compensation. In addition, independent training and compensation also have a positive and significant effect on teacher performance. Although the direct effect of academic supervision on teacher performance is not significant, there is a significant indirect effect through compensation. Thus, compensation acts as an intervening variable that strengthens the relationship between academic supervision and independent training on teacher performance. This study recommends that schools improve the quality of academic supervision, encourage independent teacher training, and provide fair compensation to support continuous improvement in teacher performance